We Fall In Love With People We Can’t Have: Patah Hati dalam teks Syair Surat Kirim Kepada Perempuan - Hanifah Yulia Sari; Dhini Yustia Widhyah; Aditya Rachman; Diantri Seprina Putri (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Frederick Clark Prescott (1922) in his book entitled The Poetic Mind states that the values contained in poetry have good therapeutic elements for troubled souls. Poetry as a literary work is believed to have elements of healing for troubled souls. One of the healing methods is by using the medium of poetry, which is known as Psychopoetry or poetry therapy. This study aims to reveal the concept of love without end or the popular concept of we fall in love with people we can't have which is contained in the text of the Syair Surat Kirim Kepada Perempuan, which is analyzed using poetry therapy studies. There are two methods used in this study, namely the philological method and the qualitative descriptive method. The philological method needs to be carried out considering that the object of this research is classical Malay literary texts. After interpreting the object, data collection uses a qualitative descriptive method. After the data has been collected, an analysis of the data is carried out using descriptive analytic methods. The result of this study is that the elements of writing poetry as a therapy for healing a wounded soul are found in the SSKKP text. Apart from that, the SSKKP text also fulfills the crucial elements of using poetry therapy to heal wounded souls.